Postfeminist biopedagogies of Instagram: young women learning about bodies, health and fitness. Issue 6 (24th July 2019) - Camacho-Miñano, Maria José; MacIsaac, Sarah; Rich, Emma
ABSTRACT: Social media can become a site of public pedagogy (Rich, E., & Miah, A. (2014). Understanding digital health as public pedagogy: A critical framework. Societies, 4 (2), 296–315. doi:10.3390/soc4020296 ) through which young people learn about health and fitness. Photo and video-sharing social networks are emerging as sites of media practices through which images of the perfect fit body circulate, popularly known as 'fitspiration' media. Our research examines how girls and young women negotiate contemporary discourses around body, health and fitness circulating through Instagram and the subjectivities such technology enables. We draw on participatory and collaborative research with young women from three Spanish Secondary schools who each engaged with exercise-related content on Instagram and who self-defined as physically active. Focus groups and semi-structured interviews explored participants' uses, meanings and influences of this digital content over their embodiment and subjectivities. Through the concept of 'postfeminist biopedagogy', we articulate the learning processes that girls experience as they engage with media about 'fit' female bodies on Instagram. This involves a series of pedagogical micro practices through which girls learn about the health and fitness subject and which bring together a postfeminist sensibility (Gill, R. (2007). Postfeminist media culture: Elements of a sensibility. European Journal of Cultural Studies, 10 (2), 147–166. doi:10.1177/1367549407075898 ), neoliberal notions of the self and discourses of health consumption. A postfeminist biopedagogy (Wright, J. (2009). Biopower, biopedagogies and the obesity epidemic. In J. Wright, & V. Harwood (Eds.), Biopolitics and the 'obesity epidemic': Governing bodies (pp. 1–14). New York, NY: Routledge) instructs and regulates girls' bodies and health subjectivities through a language of choice, empowerment and health although, at the same time, framing exercise as disciplined work to achieve the normative body. Although participants criticized such representation of the perfect body, they considered these normative pressures as necessary to 'successful' identities in postfeminist times. Our analysis reveals how some young women learn about exercise as 'aesthetic labour' through the biopedagogies circulating on Instagram, with continual work upon the body associated with performing subjectivities which are confident, happy and powerful. We conclude by exploring the implications of our findings for Physical and Health Education and young women's wellbeing.